2019
DOI: 10.3390/foods8080289
|View full text |Cite
|
Sign up to set email alerts
|

Patagonian Berries: Healthy Potential and the Path to Becoming Functional Foods

Abstract: In recent years, there has been an increasing interest in studying food and its derived ingredients that can provide beneficial effects for human health. These studies are helping to understand the bases of the ancestral use of several natural products, including native fruits as functional foods. As a result, the polyphenol profile and the antioxidant capacity of the extracts obtained from different Patagonian native berries have been described. This review aims to provide valuable information regarding fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 122 publications
0
31
0
1
Order By: Relevance
“…Among non-flavonoids there are two subgroups: non-carboxylic phenols and phenolic acids (derived from benzoic acid and cinnamic acid). [31][32][33][34][35] These compounds are not considered to have a nutritional function, nor are they essential for human health, but they can have a significant impact in preventing, delaying the onset, or ameliorating the effects of some diseases. 36 Polyphenols constitute the majority of secondary metabolites in berries.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among non-flavonoids there are two subgroups: non-carboxylic phenols and phenolic acids (derived from benzoic acid and cinnamic acid). [31][32][33][34][35] These compounds are not considered to have a nutritional function, nor are they essential for human health, but they can have a significant impact in preventing, delaying the onset, or ameliorating the effects of some diseases. 36 Polyphenols constitute the majority of secondary metabolites in berries.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…In maqui, delphinidin-and cyanidin-were the most abundant derivatives identified. 22,34,35,40 The profile and polyphenolic composition of calafate berries was identified by HPLC-MS showing that anthocyanins contribute to the major part of the polyphenolic richness of this fruit. 12 The profile also revealed that most polyphenols are in a conjugated form (glucoside and / or galactoside conjugates)that is, as glycosides, mainly as anthocyanins of the 3-glucoside type.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…As part of the diets, many fruits of native species have been used as a traditional medicine in the South American region [1,2]. The Chilean trees, arrayan [Luma apiculata (DC.)…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the consumption of fruits with a high level of antioxidants, especially anthocyanins, has been proposed as a good option to reduce the risk of chronic diseases development (Battino et al 2019;Muceniece et al 2019). Therefore, several studies have recently focused on chemoprotective properties of Chilean native berries, particularly rich in anthocyanins, which have gained quickly the interest of researchers around the world (Cespedes-Acuña et al 2018;Fuentes et al 2019;Mariangel et al 2013;Ramirez et al 2015;Ruiz et al 2013a).…”
Section: Introductionmentioning
confidence: 99%